Method of Diagnosing Functional Competence Education Managers to Perform Control and Diagnostic Functions - Marianna Torgan (Pedagogical Discourse, 2013)
The article describes particular qualities of methods of functional competence. Diagnosis of educational managers for performance of control and diagnostic functions in middle school. The proposed method involves two areas of diagnosis: the first – diagnosis of knowledge and skills, the second – diagnosis professionally important qualities of education managers. Presented a series of tasks («A», «B», «C» – for the former, psychological techniques – for the second direction), and the technology of their assessment. The results of a study to identify the level of functional competence of managers of education to carry out control and diagnostic functions of the proposed method are analyzed.